MASYARAKAT DAN PEMBANGUNAN DESA (STUDI TENTANG PERUSAHAAN COSMIC DALAM PEMBANGUNAN DI DESA TUALANG KECAMATAN TUALANG KABUPATEN SIAK) - Devi, Sri; ", Muchid (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2015)
PT. COSMIC is a company engaged in the manufacture and marketing of asphalt, emulsified, lubricating oil, and fuel oil. Currently has several representative offices in Indonesia, including in Batam, Perawang and Pekanbaru. PT. COSMIC has had some tankers to facilitate transport, for fuel terminals have had it in Batam and Pekanbaru Perawang. In the transport and distribution of PT. COSMIC use some form of land transport colt diesel, ankle, trailers and others, each of which has a payload capacity of an average of over 12 tons. The existence of public complaints against PT Cosmic vehicles passing through Jalan Waja Wangsa village Tualang tonnage exceeding got the attention of the District Government Tualang. In order to find a solution, the District Government Tualang invite companies, related parties held a meeting on hall district office Tualang order to find solutions related to how the relationships, roles, and their attitude and response and participation of all parties in addressing this issue. Meetings are held until the end of 2014 does not go realization in accordance with the agreements that have been made.For that conducted research on SOCIETY AND DEVELOPMENT VILLAGE (STUDY OF COSMIC IN ITS DEVELOPMENT IN THE VILLAGE OF TUALANG SUB DISTRICT TUALANG). This study used a qualitative, in this case the analysis, observation and interviews. The result of research on this problem is less well demonstrated by the value of relationships, roles and cooperation between PT. Cosmic, government and society.Keywords: CSR (Corporate Social Responsibility), Qualitative Analysis